2022
DOI: 10.3390/jcm11237235
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Oral Cancer Patients in Greek Clinical Practice: A Cohort Study

Abstract: Cancer of the oral cavity is one of the most common cancers all over the world. Oral cancer and its treatment impacts on patients’ Quality of Life (QOL). The purpose of the present study was to assess oral cancer patients’ QOL after the completion of surgical therapy, and to investigate factors affecting it. This was a prospective cohort study, conducted at the Department of Oral & Maxillofacial Surgery, of a large general public hospital in Northern Greece. The sample consisted of 135 consecutive eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
3
0
0
1
Order By: Relevance
“…It was observed that there is a statistically significant difference between the longitudinal assessments of all Symptom Indexes ( p < 0.0005). The fact that there exists a statistically significant difference in the EORTC-QLQ 30 subscales scores is consistent with the existing literature, reinforcing the established understanding in the field [ 15 ].…”
Section: Resultssupporting
confidence: 85%
“…It was observed that there is a statistically significant difference between the longitudinal assessments of all Symptom Indexes ( p < 0.0005). The fact that there exists a statistically significant difference in the EORTC-QLQ 30 subscales scores is consistent with the existing literature, reinforcing the established understanding in the field [ 15 ].…”
Section: Resultssupporting
confidence: 85%
“…The present results demonstrated the highest impairment in the burden of illness domain, indicating a high burden due to the cancer disease, which is in line with previous reports [74]. In this present study population, a high symptom burden correlated with high frailty and comorbidity, which are associated with the adverse side effects of the primary therapy, restricted oral functions, and impaired oral rehabilitation ability [78]. In the present results, this is supported by the highest burden in patients with the need for prosthetic treatment and RCL 4.…”
Section: Cga and Qol Impairments In Patients With R/m Hnscc Were High...supporting
confidence: 92%
“…In terms of ethnicity, Han nationality was the most affected in this study, followed by other minority groups, which could be related to the fact that most of the local permanent residents were Han. In terms of pathological types of cervical cancer, there were also differences among different countries and nationalities, but the differences were not significant [18,19]. Among the subjects of this survey, squamous cell carcinoma accounted for a large proportion (72.6%), which was consistent with the fact that squamous cell carcinoma was also the most common cancer in China [20,21].…”
Section: Implications and Comparison With Literaturessupporting
confidence: 63%